Local Elements at Colonial Buildings in Bantaeng - H Hasrianti; M. Irfan Mahmud (Pascasarjana ISBI Bandung Conference Series, 2025)
Bantaeng city contains many buildings that are remnants of the Dutch colonial period. Some of them are former residences of Dutch officials and government offices. The strong colonial architectural features are known to be integrated with traditional elements, reflecting the resilience of local culture. This research provides additional knowledge about evidence of cultural acculturation as a form of local cultural resilience in the archipelago. The data were obtained using desk study methods, qualitative reasoning, and a multidisciplinary approach. The study results showed local cultural elements in the roof, decoration, and building space formation. The use of traditional architectural elements is an effort to adapt to local geographic, climate, and cultural conditions, making buildings more resistant to tropical weather, providing thermal comfort to their occupants, and symbolising power. Keywords: Architecture; local genius; adaptation; cultural resilience